2016
DOI: 10.1093/sf/sow075
|View full text |Cite
|
Sign up to set email alerts
|

The Media as a Dual Mediator of the Political Agenda–Setting Effect of Protest. A Longitudinal Study in Six Western European Countries

Abstract: T he study investigates the impact of media coverage of protest on issue attention in parliament (questions) in six Western European countries. Integrating several data sets on protest, media, and political agendas, we demonstrate that media coverage of protest affects parliamentary agendas: the more media attention protest on an issue receives, the more parliamentary questions on that issue are asked. The relationship, however, is mediated by the issue agenda of mass media more generally, attesting to an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
3

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 57 publications
(56 reference statements)
0
32
0
Order By: Relevance
“…Also the effects of framing efforts by social movements on authorities and indirectly on political decision-making and policy changes deserve more attention. The question whether movements matter politically has become one of the most prominent ones in our field (see Chapter 25 by Amenta, Andrews, and Caren, in this volume) and studies have demonstrated the agendasetting power of protest (Vliegenthart et al 2016). Given the centrality of framing in most aspects of the movement's existence, it is likely that effects are not limited to what movements protest about, but also how they communicate about those issues, which cuts to the heart of framing.…”
Section: Resultsmentioning
confidence: 99%
“…Also the effects of framing efforts by social movements on authorities and indirectly on political decision-making and policy changes deserve more attention. The question whether movements matter politically has become one of the most prominent ones in our field (see Chapter 25 by Amenta, Andrews, and Caren, in this volume) and studies have demonstrated the agendasetting power of protest (Vliegenthart et al 2016). Given the centrality of framing in most aspects of the movement's existence, it is likely that effects are not limited to what movements protest about, but also how they communicate about those issues, which cuts to the heart of framing.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, public opinion can be an important ally for protesters. Research has identified an agenda setting effect of protest (Vliegenthart et al, 2016; see also; Walgrave and Vliegenthart 2012; Hutter and Vliegenthart 2018) and an 'amplification mechanism' and 'joint-effect' model (Agnone 2007;Giugni 2007; that work well in earlier stages of the policy process.…”
Section: To What Signals Does Mental Health Policy Respond?mentioning
confidence: 99%
“…Such a view of political conflict is most prominent in the agenda‐setting literature, and recent contributions from that tradition emphasise the power of protest to signal discontent and raise the salience of certain issues in more institutionalised arenas (e.g., Vliegenthart et al. ). In addition, the pressure from below tends to strengthen the opposition and other allies of the protesting groups in the political system, which may be the main reason why opposition parties support or even create such protest in the first place.…”
Section: Theoretical Framework and Expectationsmentioning
confidence: 99%